Hardiness and situation efficacy at elite basketball players - Sindik, J.; Adzija, M. (Collegium Antropologicum, 2013)
The main aims of the study were: to explore the latent structure of the construct of hardiness at Croatian top basketball players and to gain an understanding of the relationship between obtained hardiness dimensions and situation-related efficacy in basketball. Situation efficacy of individual basketball players in top teams is linked to the constellation of a number of relevant anthropological and specific psychological features that influence the behavior of basketball players in stressful situations during training, and especially during basketball games. One of the most important psychological characteristics for the resistance of an individual to these kinds of stress is hardiness. In the research is used a Short Hardiness Scale (SHS), which is metrically adapted to the sample of Croatian top basketball players. The questionnaire was applied to a group of 107 top basketball players, independently in all nine A-1 Croatian basketball league teams. The correlations of the hardiness dimensions with the standard and derived parameters of basketball players` situation efficacy are established, as well as with log variables. The analysis of instrument latent structure for hardiness measurement indicates the existence of two dimensions characteristic for the Croatian sample of top basketball players, which could be interpreted as a challenge and a control - commitment. A relatively small percentage of the explained variance (about 40%) suggests the possibility of defining the concept of hardiness specific for basketball situations. Low but statistically significant positive correlations were found between the dimension of control - commitment and a larger number of standard and derived parameters of situation efficacy. Statistically significant correlations between the dimension of challenge and the situation efficacy parameters or log variables are not found. This study has the main importance in cultural adjustment of hardiness to Croatian top basketball players, providing additional information about the relationship of hardiness and situation-related efficacy in basketball.